The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.4236/ojf.2012.24030
|View full text |Cite
|
Sign up to set email alerts
|

Power, the Hidden Factor in Development Cooperation. An Example of Community Forestry in Cameroon

Abstract: This paper is concomitant with our comparative study analysis of the interests and power of the stake-holders involved in Community Forestry (CF) in six countries. The study hypothesises that, “governance processes and outcomes in CF depend mostly on interests of the powerful external stakeholders”. For this paper which is on CF in Cameroon, the study hypothesizes that, “Power is a hidden factor in Development cooperation”. Based on political theories, the paper uses the “actor-centered power” (ACP) concept of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 27 publications
1
13
0
1
Order By: Relevance
“…Power, which is considered "a hidden factor in development assistance", is evident in MCNP, where external stakeholders have become more influential, while local stakeholders are powerless with no option, but to follow reluctantly. This paper supports Movuh and Schusser [15], who show that MINFOF and GIZ are powerful influential actors determining the outcomes of natural resource management projects in the South West Region (SWR). While local communities are relying on unchecked information from these influential stakeholders, they still comply without checking alternatives because they trust MINFOF-SWR, who also trusted GIZ and the accepted management conditions laid down by them without checking for alternatives.…”
Section: Ownership Control Decision-making and Project Benefactorssupporting
confidence: 60%
See 1 more Smart Citation
“…Power, which is considered "a hidden factor in development assistance", is evident in MCNP, where external stakeholders have become more influential, while local stakeholders are powerless with no option, but to follow reluctantly. This paper supports Movuh and Schusser [15], who show that MINFOF and GIZ are powerful influential actors determining the outcomes of natural resource management projects in the South West Region (SWR). While local communities are relying on unchecked information from these influential stakeholders, they still comply without checking alternatives because they trust MINFOF-SWR, who also trusted GIZ and the accepted management conditions laid down by them without checking for alternatives.…”
Section: Ownership Control Decision-making and Project Benefactorssupporting
confidence: 60%
“…Projects designed for village development plans included pipe-borne water, farm-to-market roads and crop preservation facilities. A financial agreement was signed between Cameroon (Ministry of Finance and MINFOF) and Germany (GIZ) as a development aid for sustainable management of natural resources within the South West Region (SWR), and €7,000,000 was disbursed [15]. The aim was to sustainably manage forest, promote community participation and alleviate poverty, but this has also increased the grip of MINFOF over local communities.…”
Section: Background Of Mcnp Conservation Projectsmentioning
confidence: 99%
“…A contrasting result was found for a community forestry study in Nepal [72], where the Forest Department enjoyed the highest level of coercion power. However, three power elements were used by the Ministry of Forestry in Cameroon [76], Namibia [74] and Forest Department in Indonesia [73]. Meanwhile, this research found that the Forest Department utilizes the highest level of dominant information and incentives power.…”
Section: Significance Of Power Elements In the Leading Bureaucraciesmentioning
confidence: 99%
“…The sources of power of these three elements are specific and observable, and offer the opportunity for collecting empirical data [62,71]. The actor-centered power approach, which is used in this research, has already been tested within several cases in Nepal [72], Indonesia [73], Namibia [74], Germany [75] and Cameroon [76]. The observable facts or sources of action are labeled best in a policy program, by way of allocating the tasks among the relevant bureaucracy.…”
Section: Bureaucratic Politics and Actor-centered Powermentioning
confidence: 99%
“…While the theory has already been applied in many community forestry studies across many countries (Devkota 2010, Maryudi et al 2012, Yufani Movuh and Schusser 2012, Schusser 2013, Schusser et al 2015, lately it has also been used in studies on the implementation of the international forest regime complex at national level (Brockhaus et al 2014, Mohammed and Inoue 2014.…”
Section: Power Theorymentioning
confidence: 99%